Comprei pela garrafa: a estética dos rótulos de vinho e os imaginários de consumo - Seixas, Stella Carbonell (2024)
This research aims to investigate, based on an articulation between aesthetics, imaginary and consumption, how elements of the imaginary historically associated with wine consumption participate/influence the contemporary experience of consumption, and how they manifest themselves in the choice of a wine label. An age range was made from 18 to 28 years old to characterize the young wine consumer and a geographic range related to the Brazilian public, more specifically residing in the city of São Paulo. As theoretical frameworks, the theories of the Imaginary according to Gilbert Durand (2012) and the notion of Imaginary Technologies formulated by Juremir Machado da Silva (2003) were used to explore the dimension of the wine imaginary. The concepts of Artist Capitalism by Gilles Lipovetsky and Jean Serroy (2015), and the aesthetic categories of Sianne Ngai (2010) were also worked on as a basis for the discussion on the relationships between aesthetics and consumption proposed by the research, as well as with the Movement of Cultural Meaning of Consumer Goods, described by Grant McCracken (2007), as a fundamental theory to explore the logic of consumption. The methodological process was based on the Narrativas do Vivido by Juremir Machado da Silva (2003), with the realization of a focus group (Gaskell, 2003). As the main results of the research, it is understood that wine is an object that still sustains its value through traditionality; that the label does not play such a relevant role in shaping the imagination and that the statement “I bought it for the bottle”, repeated so many times during the focus group, does not mean that the consumer necessarily gravitates towards labels with more creative designs.